Efficacy and safety of maintenance olaparib and bevacizumab in ovarian cancer patients aged ≥65 years from the PAOLA-1/ENGOT-ov25 trial. (March 2023) - Sabatier, Renaud; Rousseau, Frédérique; Joly, Florence; Cropet, Claire; Montégut, Coline; Frindte, Johanna; Cinieri, Saverio; Guerra Alía, Eva M.; Polterauer, Stephan; Yoshida, Hiroyuki; Vergote, Ignace; Colombo, Nicoletta; et al.
Abstract: Background: The phase III PAOLA-1/ENGOT-ov25 study (NCT02477644) showed that addition of olaparib to bevacizumab maintenance improved progression-free survival (PFS) in patients with newly diagnosed advanced ovarian cancer. We evaluated maintenance olaparib plus bevacizumab in older patients in PAOLA-1. Methods: Baseline clinical and molecular data, and PFS, were compared between older (aged ≥65 years) and younger patients (<65 years). Factors associated with olaparib efficacy, and safety in age subgroups, were also assessed. Results: Of 806 randomised patients, 292 (36.2%) were ≥65 years. A lower proportion of older versus younger patients had an Eastern Cooperative Oncology Group performance status of 0 (61.0% versus 76.2%) and upfront surgery (42.0% versus 55.7%). Older patients were less likely to have a BRCA1/2 mutation (17.1% versus 36.7%) or homologous recombination deficiency-positive status (34.1% versus 55.7%). After median follow-up of 22.1 months, median PFS was 21.6 months with olaparib versus 16.6 months with placebo in the older population (hazard ratio [HR] 0.55, 95% confidence interval [CI] 0.41–0.75), comparable with the younger population (median 22.9 versus 16.9 months; HR 0.61, 95% CI 0.49–0.77). PFS benefits were observed in patients with a BRCA mutation or homologous recombination deficiency-positive tumours. Incidence of olaparib-related grade ≥3 adverse events in older patients was comparable with that of younger patients (36.8% versus 31.7%) although hypertension and anaemia were more common in older patients. No treatment-related deaths occurred in older patients receiving olaparib. Conclusion: Older patients enrolled in PAOLA-1 achieved similar PFS benefits compared with younger patients, with a similar safety profile. Highlights: Older patients in PAOLA-1 had unfavourable baseline clinical and molecular features. Benefits of olaparib plus bevacizumab were similar in older and younger patients. Improved progression-free survival was limited to those with HRD-positive tumours. Safety and tolerability profiles were similar in older and younger patients.